2023
DOI: 10.3390/su15021520
|View full text |Cite
|
Sign up to set email alerts
|

Study on Joint Distribution Mode and Evolutionary Game of Express Enterprises in Rural Areas

Abstract: Express delivery in rural areas of China has many problems, such as high delivery cost and low efficiency. As an effective way to solve the difficulties of rural delivery, it is important to study the innovation and application of a joint distribution model. In the background, this paper takes express delivery enterprises in rural areas as the research object. First, it proposes to construct a three-level “county-town-village” joint distribution system in which e-commerce platforms participate. Next, it establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Hu [28] found that a good social network relationship is helpful to the digital diffusion of enterprises in the process of exploring the digital performance of enterprises based on social network theory. Zhao and Li [29] proposed to build a three-level 'county, township, and village' joint distribution system with the participation of e-commerce platforms. They first established and solved an evolutionary game model of a joint distribution alliance of express delivery enterprises.…”
Section: Related Researchmentioning
confidence: 99%
“…Hu [28] found that a good social network relationship is helpful to the digital diffusion of enterprises in the process of exploring the digital performance of enterprises based on social network theory. Zhao and Li [29] proposed to build a three-level 'county, township, and village' joint distribution system with the participation of e-commerce platforms. They first established and solved an evolutionary game model of a joint distribution alliance of express delivery enterprises.…”
Section: Related Researchmentioning
confidence: 99%
“…This study aims to establish an index system through systematic analysis and optimization methods and use the gray comprehensive evaluation model to evaluate the core competitiveness of Zhongtong, Yuantong, Shentong, and Yunda Express, which are listed express delivery companies in China, under the current Internet-based economic environment. The analysis of the gray correlation method was as follows: first, establish a model of influencing factors that affect the development of the express delivery industry; then, quantify the indicators of each influencing factor and establish their initial value; and, finally, use a numerical calculation method to find the weight of each influencing factor, and then according to the empirical analytical results, focus on analyzing the competitiveness between Yunda, Yuantong, Shentong, and Zhongtong Express, as well as the most critical factors affecting the development of the express delivery industry [2][3][4].…”
Section: Introductionmentioning
confidence: 99%